Desarrollo de una Aplicación y Procedimiento para Control de Costos de los Proyectos Constructivos de KIREBE - Ramírez-Fallas, Olman (Instituto Tecnológico de Costa Rica, 2008)
KIREBE´s company was presenting problems for the deficient managing of control of costs that was carried out in its constructive projects; that’s because, the practice directed was realized here, and look for deficiencies that this process had and to give them a solution. Part of this labour, was investigate on the procedures used by each of the departments and principally in circumstances that were involving the Cost department. As well as also, explore on the way of executing that the department of costs had at the moment. Principally, problems like mistake of instructives, programming of work, communication and the storage of information of requisitions, modifications and unforeseen situations, were found during the realized research and it was not allowing to conclude on the advance that project had. Therefore, by information found, it was possible to develop a new procedure of control of costs and an application computacional that was facilitating the obtaining of information; and in a consecutive way, they were serving for the posterior analysis on the advance of the project. A suitable mechanism of control of costs adjusted to the way of working of the company, with communication and teamwork, is possible to achieve the success of the project and in consequence the company.
Proyecto de Graduación (Licenciatura en Ingeniería en Construcción) Instituto Tecnológico de Costa Rica. Escuela de Ingeniería en Construcción, 2008.
Keywords: Proyecto; Limitantes; Construcción; Presupuesto; Retroacción